Faktor Apakah Yang Memicu Transaksi Pihak Berelasi - Nahumury, Joicenda; Agus Irwandi, Soni (Universitas Dian Nuswantoro, 2024)
The purpose of this research is to examine the ownership structure and firm size to the related party transactions. Population of this research were all companies of consumer non-cyclicals which had listed at the Indonesian Stock Exchange during period 2018-2022. A total of 212 research samples was selected using cluster random sampling technique. The Research method use quantitative analysis approach. Analysis techniques to test the hypothesis was the model of the structural warp PLS 7.0 . The result of this research described that ownership structure has significant effect to the related party transactions and firm size have no effect to the related party transactions